Properties of High-Calcium Fly Ash Geopolymer Paste Mixed with Ground Clay Brick - Nasaeng, Phaithun; Wongsa, Ampol; Sata, Vanchai; Chindaprasirt, Prinya (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
This research aimed to study the properties of geopolymer paste using high calcium fly ash mixed with ground clay brick. The main raw material used was high-calcium fly ash from Mae Moh Power Plant, Lampang Province. Ground clay brick was used to partially replace high calcium fly ash at the ratios of 0, 25, 50, 75, and 100 by weight. Sodium silicate and 10 molar of sodium hydroxide solutions were used as alkali solutions at the ratio of 1.00. The alkali liquid to solid powder ratio was kept constant for all mixes at 0.60. The flow value, setting time, compressive strength, and microstructure analysis by SEM/EDS, XRD, and FTIR of the geopolymer paste were tested. The results showed that ground clay brick had highly crystalline silica materials. An increase in the number of ground clay bricks increased the setting time while the flow value and compressive strength decreased. The microstructural analysis showed that the C-S-H or C-A-S-H compounds and geopolymer gels were formed in the geopolymer pastes. When high-calcium fly ash was replaced with ground clay brick, more crystals and non-reactive particles were generated, which negatively affected the mechanical properties at an early age. However, the replacement at a rate of 25 - 50 % had slightly lower 60-day compressive strength than the control sample.